THE ROLE OF RISK CULTURE IN SMEs WHO OPERATE IN THE GJIROKASTRA REGION - Lorenc Koçiu; Robert Çelo; Romeo Mano (European Scientific Journal, ESJ, 2015)
SMEs face tough competiton in their market, with obstacles and barriers affecting various aspects of their day –to –day activity, such as, launching and marketing new products, taking market shares away from existing and new SMEs. This is because of many reasons, ranging from their size, limited financial resources and constraints in hiring qualified personnel compared to larger enterprises. The nature of the risks faced by SMEs in their everyday activity affecting the decision making process, right implementation practices, employing the right people, and other related issues is very different from the risk faced by large businesses. In this article we will try to identify and highlight the impact of risk culture in the activity and performance of SMEs. With the aim of trying to present a complete picture of the situation we will analyse SMEs in the Gjirokastra region, focusing on their organizational framework with the purpose of identifying and highlighting the risk culture. Primary data used in this research is gathered through structured questionnaires, addresed to a number of executives. Furthermore we categorise the economic enterprises based on criteria such as number of employees, turnover, year of establishment etc, in order to facilitate the work to be done regarding the highlighting and assessing of risk culture. Moreover, we have also consulted foreign literature, which provided us with plenty of relevant information. Albanian literature regarding the identification and assessment of risk culture is very scanty, almost inexistent. At the end of this paper we reach several conclusions and make valuable recommendations regarding the most effective management of risk culture.